Relationship between temperature and the timing of breeding of the blue tit (Parus caeruleus) in two Mediterranean oakwoods - Bellot, M D; Dervieux, Alain; Isenmann, Paul (Journal of Ornithology, 1991)
They think that these temperatures have an influence on the timing of breeding but it remains unclear if this influence is direct or indirect. In this study, we present the results of an investigation of the effect of temperature on the timing of breeding of a population of Blue Tits (Parus caeruleus) breeding in two neighbouring oakwoods, one dominated by evergreen Holm Oaks, the other by deciduous Downy Oaks in Mediterranean France. Though experiencing the same climate, this population shows marked variation between individuals for laying time (BLoNDEL et al. 1987, CLAMENS & ISENMANN 1989, DERVIEUX et al. 1990). In this con- text, two questions are considered: 1) is there a relationship between temperature and laying date in the two oakwoods and, 2) how may temperature cause such variation?
Keywords: breeding; egg laying; Parus caeruleus (voyant); Temperature